Myoclonic epilepsy in Down syndrome and Alzheimer disease - J.S. Aller-Alvarez; M. Menéndez-González; R. Ribacoba-Montero; M. Salvado; V. Vega; R. Suárez-Moro; M. Sueiras; M. Toledo; J. Salas-Puig; J. Álvarez-Sabin (Neurología (English Edition), 2017)
Introduction: Patients with Down syndrome (DS) who exhibit Alzheimer disease (AD) are associated with age. Both diseases with a common neuropathological basis have been associated with late-onset myoclonic epilepsy (LOMEDS). This entity presents electroencephalogram features as generalised polyspike-wave discharges. Method: We present a series of 11 patients with the diagnosis of DS or AD who developed myoclonic seizures or generalised tonic–clonic seizures. In all cases, clinical and neuroimaging studies and polygraph EEG monitoring was performed. Results: In all cases, cognitive impairment progressed quickly after the onset of epilepsy causing an increase in the degree of dependence. The most common finding in the EEG was a slowing of brain activity with theta and delta rhythms, plus intercritical generalised polyspike-waves were objectified in eight patients. In neuroimaging studies was found cerebral cortical atrophy. The most effective drug in this series was the levetiracetam. Conclusions: The association of generalised epilepsy with elderly DS represents an epiphenomenon in evolution which is associated with a progressive deterioration of cognitive and motor functions. This epilepsy has some electroclinical characteristics and behaves as progressive myoclonic epilepsy, which is probably related to the structural changes that characterise the evolutionary similarity of DS with AD. Recognition of this syndrome is important, since it has prognostic implications and requires proper treatment. Resumen: Introducción: Los pacientes con síndrome de Down (SD) presentan una demencia tipo Alzheimer (EA) asociada a la edad. Ambas patologías, con una base neuropatológica común, han sido asociadas a la epilepsia mioclónica de inicio tardío (LOMEDS). Esta entidad presenta alteraciones electroencefalográficas características en forma de descargas generalizadas de polipunta-onda. Método: Presentamos una serie de 11 pacientes con el diagnóstico de SD o EA que desarrollaron crisis epilépticas mioclónicas o tónico-clónicas generalizadas. En todos ellos, se realizó un seguimiento clínico y estudios de neuroimagen y poligrafía EEG. Resultados: En todos los casos, el deterioro cognitivo avanzó rápidamente tras el comienzo de la epilepsia, produciendo un incremento en el grado de dependencia. El hallazgo más común en el EEG fue un enlentecimiento de la actividad cerebral con ritmos theta y delta; además, en 8 pacientes se objetivaron descargas intercríticas generalizadas de polipunta-onda. En los estudios de neuroimagen se encontró atrofia cerebral cortical. El fármaco más eficaz en esta serie fue el levetiracetam. Conclusiones: La asociación de epilepsia generalizada al SD de edad avanzada supone un epifenómeno en la evolución que marca un agravamiento rápidamente progresivo de las funciones cognitivas y motoras. Presenta unas características electroclínicas bien definidas y se comporta como una epilepsia mioclónica progresiva, que probablemente se relaciona con los cambios estructurales que caracterizan el parecido evolutivo del SD con la enfermedad de Alzheimer. El reconocimiento de este síndrome es importante, dado que tiene repercusiones pronósticas y requiere un tratamiento adecuado. Keywords: Down syndrome, Alzheimer's disease, Myoclonic epilepsy, Dementia, Late-onset myoclonic epilepsy in Down syndrome, Palabras clave: Síndrome de Down, Enfermedad de Alzheimer, Epilepsia mioclónica, Demencia, Late-onset myoclonic epilepsy in Down syndrome